Common Deviations from Standard Phraseology among Indonesian Pilots and Air Traffic Controllers - Gharibnavaz, Sajjad; Agustina, Noni (Foremost Journal, 2026)
Ensuring the flight safety, it requires clear and standardized pilot-controller communication through ICAO phraseology. However, deviation still exists in routine operations. Thus, this study examines deviations from ICAO standard phraseology among Indonesian pilots and air traffic controllers (ATCs) by identifying the types and prevalence of these deviations and to explore the underlying reasons behind their use in operational communication. A qualitative design was employed, using an open-ended questionnaire and semi-structured interviews with licensed Indonesian pilots and ATCs. The questionnaire was used to capture and quantify reported deviations, while the interviews explored factors shaping participants’ communication choices. The findings showed that, although both pilots and ATCs were aware of ICAO standards, deviations occurred frequently in day-to-day operations. Common deviations involved the pronunciation of letters and numbers, as well as the transmission of wind information, radar beacon codes, altitude, altimeter settings, frequency, time, and aircraft registration/call signs. The primary reasons for these deviations included habitual use, perceived efficiency, local adaptation, and occasional memory lapses. These results highlight the need for ongoing training and sustained awareness efforts to strengthen standardized communication and support operational safety.